Analysis of wind to hydrogen production and carbon capture utilisation and storage systems for novel production of chemical energy carriers. (20th June 2022) - Henry, Ashleigh; McCallum, Chris; McStay, Daniel; Rooney, David; Robertson, Peter; Foley, Aoife
Abstract: As the offshore energy landscape transitions to renewable energy useful decommissioned or abandoned oil and gas infrastructure can be repurposed in the context of the circular economy. Oil and gas platforms, for example, offer opportunity for hydrogen (H2 ) production by desalination and electrolysis of sea water using offshore wind power. However, as H2 storage and transport may prove challenging this study proposes to react this H2 with the carbon dioxide (CO2 ) stored in depleted reservoirs. Thus, producing a more transportable energy carriers like methane or methanol in the reservoir. This paper presents a novel thermodynamic analysis of the Goldeneye reservoir in the North Sea in Aspen Plus. For Goldeneye, which can store 30 Mt of CO2 at full capacity, if connected to a 4.45 GW wind farm, it has the potential to produce 2.10 Mt of methane annually and abate 4.51 Mt of CO2 from wind energy in the grid. Highlights: Opportunity for overlap of wind and oil and gas in North Sea to make green hydrogen. Green hydrogen can be combined with carbon dioxide in depleted reservoirs. Methane production favoured at conditions of Goldeneye reservoir in North Sea. Thermodynamic model shows more hydrogen in feed increases methane production. Associated carbon and financial savings increase feasibility.